Role of Saccharomyces cerevisiae Fcy Proteins and Their Homologs in the Catabolism of Modified Heterocyclic Pyrimidine Bases - Jaunius Urbonavičius; Iglė Vepštaitė-Monstavičė; Juliana Lukša-Žebelovič; Elena Servienė; Daiva Tauraitė (Microorganisms)
The synthesis of various heterocyclic base modifications of nucleic acids has been thoroughly investigated; however, much less is known about their catabolism. Also, little is known about the transport of such compounds across the microbial cell membranes. Using the Saccharomyces cerevisiae single-gene deletion library, we performed genome-wide screening for genes affecting the growth of yeast in minimal media supplemented with N4-acetylcytosine as a source of uracil. We found that Fcy1, Fcy21, Bud16, Gnd1, and Fur4 proteins are required for efficient growth in the tested medium. Additionally, we used several heterocyclic pyrimidine bases and Fcy homolog mutants to test their growth in respective minimal media. We found that tested permeases differently affect the growth of yeast that is dependent on the heterocyclic pyrimidine bases used as a source of uracil. The most pronounced effect was observed for the ∆fur4 mutant, which was growing much slower than the corresponding wild-type strain in the media supplemented with N4-acetylcytosine, 4-methylthiouracil, N4-methylcytosine, N4,N4-dimethylcytosine, 2-thiouracil, or 4-thiouracil. We suggest that Fur4 protein is the major yeast transporter of modified heterocyclic pyrimidine bases. Our observations might be helpful when investigating the actions of various heterocyclic base-based antifungal, anticancer, and antiviral drugs.